A Multi-Factoral Approach to Enhancing Millennial Teachers' Personal Knowledge Management - Rustiyono Rustiyonno; Sudarwan Danim; Nadia Nur ifani (Program Studi Manajemen Pendidikan Islam Institut Pesantren KH Abdul Chalim Mojokerto, 2024)
Prior research has emphasized a need for scholarly works investigating millennial instructors' knowledge management (PKM) practices at the individual level within an institution. In addition, there needs to be more research examining the role of organizational learning as a mediator between transformational leadership and personal knowledge management among millennial instructors. This study examines how transformational leadership, ICT literacy, and organizational learning affect personal knowledge management (PKM) among Indonesian school instructors in their 20s and 30s. Another goal is to investigate the function of organizational learning as a mediating factor. We administered questionnaires to 100 teachers at some private Islamic schools in Bengkulu, Indonesia, and evaluated them subsequently using partial least squares structural equation modeling. The results suggest that proficiency in information and communication technology (ICT), the ability to inspire and guide others through transformational leadership, and the presence of a culture that promotes continuous learning within the business all contribute positively to the practice of personal knowledge management (PKM) among instructors from the millennial generation. The study determined that ICT literacy had the most substantial impact on teachers' PKM. Furthermore, organizational learning mediates between transformational leadership and PKM, resulting in a slight rise. These findings have practical consequences for school administrators who aim to increase millennial teachers' information and communication technology (ICT) skills in the region. One way to achieve this is by creating an ICT literacy ecosystem within schools, which will help strengthen the personal knowledge management of these instructors.